(untitled) (Tribhuvan University Law Journal, 2025)
The International Labour Organization (hereafter referred to as, ILO) is a specialized agency of the United Nations (hereafter referred to as, UN) from 1948, focused on advancing social justice and promoting decent work worldwide. Established in 1919 as an autonomous organization of the League of Nations, the ILO sets international labour standards and fosters social dialogue to improve working conditions, employment opportunities, and workers’ rights globally through international labour instruments including, Declarations, Conventions, Protocols, and Recommendations that are adopted under its auspices. Additionally, the ILO provides technical assistance and expertise to help implement these instruments at the national level. The gravity of the contribution made by the ILO worldwide since its establishment to enhance labour rights cannot be measured in magnitude. Currently, 187 States are members of this organization. However, there varies in the number of States’ party in its Conventions and other binding instruments. For this paper, a glance at ILO’s instruments and the sufficiency and systematization of the coordination of the monitoring mechanisms for ratifying instruments are discussed. Effectively implementing international labour law within a national framework involves aligning domestic laws with international standards, ensuring compliance, and establishing robust mechanisms for enforcement and dispute resolution. In such context, the author followed the exploratory and descriptive method under the doctrinal methodology for revealing the effectiveness of the monitoring system in measuring the implementation of international labour law instruments, particularly developed under the regime of ILO. Secondly, dealt with the concept of international labour law, international labour standards, and ILO’s governance mechanism. Finally, as a reference, it dealt with the internalizing or domestication mechanism of international labour law in the Nepalese and Indian contexts. Thus, the scope of this article is limited to the domestication of international labour laws, an overview of the major organs of ILO and its monitoring and supervisory systems.